A influência de imagens indiretas como fonte de inspiração no processo criativo de design - Amaral, Laura Guidali (Universidade do Vale do Rio dos Sinos, 2013)
One of the main characteristics of the Strategic Design concept adopted in this research is the use of a design method that proposes a stage called metadesign - a space for discussion of the design problem. At this stage, a special type of tool is used, called Blue Sky research. It is essentially composed by visual references, that are external to the design context, and reveals trends and offers useful stimuli in the project. The purpose of this investigation is to reflect about the role of images not directly related to the design problems - indirect references - as inspiration sources for the creative design process. To do so, several aspects are reviewed, such as the "Wicked problem" and it's solution process; creative process; and usage of images as reference. A exploratory research, which includes the development of linkographs, is proposed in order to evaluate how these specific images are used during the project process. Evidence is presented, showing that indirect references help the formulation of conceptual ideas, by increasing the reflection time of the individuals about the problem and about the solution.
Keywords: Design; Método de projeto; Referências visuais; Design estratégico; Pesquisa Blue Sky; Design method; Visual references; Strategic design; Blue sky research; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial